Zondervan exegetical commentary on the Old Testament : Ezra - Nehemiah - Smith, Gary V. (Grand Rapids, MI, Zondervan Academic, 2022)
"The Zondervan Exegetical Commentary series provides a careful analysis and interpretation of the biblical text, rooted in a study of the Hebrew text of the Old Testament and intended to track the flow of the argument in each book and passage"--
Includes bibliographical references and indexes
Keywords: Bible. -- Commentaries; Bible. -- Commentaries